Anti‐Sm is associated with the early poor outcome of lupus nephritis. (29th April 2016) - Ahn, Sung Soo; Yoo, Byung‐Woo; Song, Jason Jungsik; Park, Yong‐Beom; Lee, Soo‐Kon; Lee, Sang‐Won
Abstract: Aim: We investigated whether anti‐Smith (Sm) is associated with the outcome of kidney biopsy‐proven lupus nephritis. Methods: We retrospectively analyzed clinical, laboratory and histological results in 90 patients with kidney biopsy‐proven lupus nephritis. We defined persistent administration of immunosuppressants for more than 3 months after the kidney biopsy as early poor outcome of lupus nephritis. We compared baseline variables and delta values of lupus nephritis‐related variables between patients with and without anti‐Sm. The independent predictive values for early poor outcome were analyzed using logistic regression analysis. Results: The median age was 32.0 years old, and 77 patients (85.5%) were women. Anti‐Sm was found in 44 of 90 patients (48.8%). When we analyzed the differences in delta values of variables reflecting the kidney function or the early poor outcome between patients with and without anti‐Sm, we found significant difference in the early poor outcome between the two groups (80.0% of patients having anti‐Sm vs . 56.5% of those not having anti‐Sm, P = 0.022). In multivariate logistic regression analysis, along with age and Systemic Lupus Erythematosus Disease Activity Index, the presence of anti‐Sm increased the potential of the early poor outcome of lupus nephritis (odds ratio 2.870, 95% confidence interval, 1.033, 7.976, P = 0.043). Conclusion: Our data suggest that anti‐Sm identified at kidney biopsy might have a predictive value for the early poor outcome of biopsy‐proven lupus nephritis during the follow‐up period.